Fear and Anxiety among patients treated by scaling in Periodontally healthy subjects - Setty, Swati; Kannur, Pooja; Thakur, Srinath L (Asian Journal of Medical Sciences, 2017)
Background: Anxiety and fear experience represent significant problems in dental practice and are the factors that discourage the demand for treatment. They affect the use of health care services, treatment decision-making, and responses to periodontal treatment. Aims and Objectives: The aim of this study was to evaluate fear and anxiety in patients undergoing scaling and root planing. Materials and Methods: Total of 80 patients were selected and grouped into 20-35 yrs and 40-55 yrs and each age group had 20 males and 20 females, so 40 were males and 40 were females. They were given a structured questionnaire dealing with dental fear and dental anxiety to fill. Statistical analysis was done by Tukey’s multiple post hoc, Two-way ANOVA and Chi –square test. Results: The mean dental anxiety score (DAS) for males was 6.67±3.24 and for females it was 6.57±2.30. The mean DAS score for 20-35yrs was 6.025±2.37 and for 40-55yrs it was 7.22±3.02. But statistically significant difference was not found in the DAS scores in both sex and age groups. The mean dental fear survey (DFS) for males was 28.9±9.4 and for females was 30.5±6.56. The mean DFS score for 20-35yrs was 28.42±8.06 and for 40-55yrs it was 30.97±7.89. But this in the DFS scores was also not found statistically significant in both sex and age groups. When DAS and DFS scores were compared, there was a statistically significant correlation. Conclusion: An understanding of the presence of the anxiety and fear can help dentists to understand what patients feel about dental treatment procedures and aid dentist efforts to improve patients care. They should treat patients and seek to avoid fear and anxiety and discomfort in their patients caused by the treatment. Asian Journal of Medical Sciences Vol.8(1) 2017 77-81